2018
DOI: 10.1097/j.pain.0000000000001355
|View full text |Cite
|
Sign up to set email alerts
|

Morphine effects within the rodent anterior cingulate cortex and rostral ventromedial medulla reveal separable modulation of affective and sensory qualities of acute or chronic pain

Abstract: Modulation of pain may result from engagement of opioid receptors in multiple brain regions. Whether sensory and affective qualities of pain are differentially affected by brain opioid receptor circuits remains unclear. We previously reported that opioid actions within the rostral anterior cingulate cortex (ACC) produce selective modulation of affective qualities of neuropathic pain in rodents, but whether such effects may occur in other areas of the ACC is not known. Here, morphine was microinjected into 3 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 60 publications
4
27
0
Order By: Relevance
“…Evoked mechanical activity was lower in the rostral anterior cingulate cortex yet higher in the rostral ventromedial medulla (RVM) reflecting functional connectivity between these two areas. These areas are in concordance with a preclinical study on morphine actions on sensory and affective pain measures in rodents (Gomtsian et al 2018). Most importantly the patient study (Soni et al 2019) revealed, in keeping with the ideas of a recruitment of the RVM facilitatory (presumably 5HT3 mediated) system in chronic pains (see Bannister and Dickenson 2016a;Bee and Dickenson 2008), that preoperative neuropathic-like pain and higher neural activity in the RVM were associated with moderate-to-severe long-term pain after arthroplasty.…”
Section: Brain Areas That Control Descending Inhibitory Pathwayssupporting
confidence: 83%
“…Evoked mechanical activity was lower in the rostral anterior cingulate cortex yet higher in the rostral ventromedial medulla (RVM) reflecting functional connectivity between these two areas. These areas are in concordance with a preclinical study on morphine actions on sensory and affective pain measures in rodents (Gomtsian et al 2018). Most importantly the patient study (Soni et al 2019) revealed, in keeping with the ideas of a recruitment of the RVM facilitatory (presumably 5HT3 mediated) system in chronic pains (see Bannister and Dickenson 2016a;Bee and Dickenson 2008), that preoperative neuropathic-like pain and higher neural activity in the RVM were associated with moderate-to-severe long-term pain after arthroplasty.…”
Section: Brain Areas That Control Descending Inhibitory Pathwayssupporting
confidence: 83%
“…Cortical neuropeptide signaling may be one such corner. While profound impacts of neuropeptide signaling are well-established in a wide range of non-mammalian and sub-cortical neural structures (Borbély et al, 2013; Burbach, 2011; Elphick et al, 2018; Grimmelikhuijzen and Hauser, 2012; Katz and Lillvis, 2014; Jan et al, 1979) and there certainly is an excellent literature on cortical neuropeptide signaling (Crawley, 1985; Férézou et al, 2007; Gallopin et al, 2006; Gomtsian et al, 2018; Hamilton et al, 2013; Liu et al, 2018; Mena et al, 2013; Mitre et al, 2018; Owen et al, 2013; Rossier and Chapouthier, 1982; Williams and Zieglgänsberger, 1981), published physiological results are surprisingly rare given the breadth of neuroscientific interest in cortex. The new transcriptomic data analyzed here suggest a possible explanation for this relative rarity.…”
Section: Discussionmentioning
confidence: 99%
“…Light from single-cell transcriptomics is now beginning to illuminate dark corners of cellular neuroscience 424 that have long resisted mechanistic and functional analysis (Fan et al, 2018;Fishell and Kepecs, 2019; may be one such corner. While profound impacts of neuropeptide signaling are well-established in a wide 428 range of non-mammalian and sub-cortical neural structures (Borbély et al, 2013;Burbach, 2011;Elphick 429 et al, 2018;Grimmelikhuijzen and Hauser, 2012;Katz and Lillvis, 2014;Kuffler et al, 1979) and there 430 certainly is an excellent literature on cortical neuropeptide signaling (Crawley, 1985;Férézou et al, 2007;431 Gallopin et al, 2006;Gomtsian et al, 2018;Hamilton et al, 2013;Liu et al, 2018;Mena et al, 2013;Mitre 432 et al, 2018;Owen et al, 2013;Rossier and Chapouthier, 1982;Williams and Zieglgänsberger, 1981), 433 published physiological results are surprisingly rare given the breadth of neuroscientific interest in cortex.…”
Section: Discussionmentioning
confidence: 99%